2014
DOI: 10.1177/1559827614522942
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Cost Comparisons of Select Canned, Frozen, and Fresh Fruits and Vegetables

Abstract: A common call to action for addressing public health concerns of both obesity and hunger is improving access to and consumption of fruits and vegetables. Previous research has examined the nutritional merits of fresh, frozen, and canned fruits and vegetables. However, there are limited data on the cost-effectiveness of fresh compared with processed-that is, canned and frozen-food. This study examined the nutrition delivered in 8 common vegetables and 10 common fruits across multiple packaging options (fresh, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 29 publications
(56 reference statements)
0
36
0
Order By: Relevance
“…For instance, fresh fruit tends to provide greater nutrient content relative to canned options. 151 It is very difficult to provide a clear-cut final answer to this question. The subject has been examined twice by the French National Food Council, in 2002 1 52 and in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, fresh fruit tends to provide greater nutrient content relative to canned options. 151 It is very difficult to provide a clear-cut final answer to this question. The subject has been examined twice by the French National Food Council, in 2002 1 52 and in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Frozen fruit can be transported to remote markets that could not be accessed with fresh fruit and can be used year-round for second-stage processing of fruit-based products (such as jams, juice and syrups) (Miller and Knudson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So, while the thermal treatment used in the canning process can result in the breakdown or transformation of some water-soluble vitamins, the remaining nutrients are much more stable over time compared to those in fresh or frozen products since there is less exposure to oxidation and microbial threats [ 6 , 7 ]. Recent research has even shown that the thermal processing techniques used in the canning process may actually preserve or enhance some nutritional qualities in nutrient-dense foods such as canned beans, vegetables and fruits when compared to fresh foods [ 4 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, fresh foods are recommended as the primary nutrient-dense dietary options, but fresh foods are not always available to all Americans due to seasonal, economic and geographic factors. Recent research has shown that canned options contain comparable nutrient profiles to fresh foods [ 4 , 5 , 6 , 7 ], therefore nutrient-dense canned foods should be considered as healthy options alongside fresh foods, or as nutritious alternatives to fresh foods. Additionally, a study by Kapica et al , provided evidence that canned foods are some of the most cost-effective and accessible nutrient options available to Americans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%